The Egg Hunt - Hunt,Roderick (Oxford university press, 1986)
The Egg Hunt" by Roderick Hunt, part of the Oxford Reading Tree series, follows Biff, Chip, Kipper, and their friends as they participate in an exciting Easter egg hunt. The children search for hidden eggs, solving clues and working together to find as many eggs as possible.
Keywords: Textbook